Pemetaan Lokasi Fishing Ground dan Status Pemanf aatan Perikanan di Perairan Selat Madura - Efendy, Mahfud; Muhsoni, Firman Farid; Triajie, Haryo; Syah, Achmad Fachruddin (Rekayasa, 2008)
This research aims atfinding out map of water quality spreading to predict fishing ground, determine catching region map, test determinant parameter modeling offish catching region, analyzefish product per catching unit (Cp UE) andfish utilization status. Method used in map water quality parameter is interpolation analysis in wide sample data, map surface temperature and chlorophyll from extract satellite image landsat. Area of catching is conducted by modeling with the application of scoring and weighting factors, accuracy test with method of RM SE. Fishery utilization status is gathered with method of holistic approach (production surplus model). Map water salinity at straits Madura is between 27 ppm - 46 ppm, pH rangefrom 8-9, brightness ranges from 0-2 m. Sea level temperature from image landsat in dry season rangesfrom 24,1 OC - 27,3 OC in rainy season between 24,7OC -28,6 OC. Optimum temperature in rainy season lower is compared in dry season. Chlorophyll in dry season between 0 mg/m3 - 19,6 mg/m3, in rainy season between -0,02 mg/m3 - 41,95 mg/m3. Map Fish catching region in season gets region very appropriate at 58,04 %,appropriate region 36,9!1% and region inappropriate 4,96 %.inappropriate region rainy season achieves 94,44 %, appropriate 2,89 % and inappropriate 2,65 %. sea level temperature accuracy test gets RM SE 2,32 and for chlorophyll pregnancy 2,31. Fishery estimation result pelagis gets CpU E 0.10 ton/trip with utilization status in indication of over-fishing in tahun1997 and fishery demersal CpU E 0.03 ton/trip with utilization status becomes surplus catches in lasl three year.